The Effect of System Quality and Information Quality on System User Satisfaction Accounting Information - Mendrofa, Meliana; Hastuti, Sri (Universitas Bhayangkara Surabaya, 2024)
This study aims to examine the effect of system quality and information quality on user satisfaction in the study of Fremilt Thai Tea outlet employees in Yogyakarta. This study uses a quantitative approach collected through primary data in the form of questionnaires distributed to respondents. The sampling method uses consideration from the researcher, so that 45 respondents are obtained, namely the total employees at the Fremilt Thai Tea outlet. The analysis technique in this study uses multiple linear regression analysis through SPSS 26 software. The results of this study indicate that 1) system quality affects user satisfaction, 2) information quality has no effect on user satisfaction.